Investors’ Awareness and Investment Factors Affecting Stock Market in Nepal - Ghemosu, Tulsi Ram (Patan Prospective Journal, 2025)
This study investigates the knowledge levels and behavioral factors that influence investor participation and decisions in Nepal’s stock market. Investing involves committing current resources for future financial gains, balancing risk and return to achieve wealth accumulation and financial security. Unlike saving, investing carries higher risks and requires informed decision making supported by research and analysis. In Nepal, many investors lack comprehensive understanding of market operations, trading processes, and risk management, aggravated by limited access to timely and accurate information. Socioeconomic and cultural factors further shape investor behavior and awareness. The research assesses investor awareness levels, significant factors shaping investment decisions, and challenges encountered by investors. Key influencers include financial knowledge and evaluation, information dissemination, education and training programs, social learning, and regulatory frameworks. Behavioral finance theories emphasize the role of psychological biases and social influences, while portfolio theory highlights risk diversification strategies. Findings indicate moderate investor awareness with a strong link between financial knowledge and informed investing. However, gaps remain in technical analysis knowledge and the reach of educational initiatives. Enhancing financial literacy, ensuring transparent information flow, and strengthening regulations are essential to empower investors and promote sustainable growth in Nepal’s capital market.